2016
DOI: 10.1159/000446247
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review and Meta-Analysis of Studies Examining the Use of Brain Laser Interstitial Thermal Therapy versus Craniotomy for the Treatment of High-Grade Tumors in or near Areas of Eloquence: An Examination of the Extent of Resection and Major Complication Rates Associated with Each Type of Surgery

Abstract: Background: The extent of resection (EOR) of high-grade gliomas (WHO grade III or IV) in or near areas of eloquence is associated with overall patient survival, but with higher major neurocognitive complications. Methods: A systematic review and meta-analysis was undertaken of the peer-reviewed literature in order to identify studies which examined EOR or extent of ablation (EOA) and major complications (defined as neurocognitive or functional complications which last >3 months duration after surgery) associat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(32 citation statements)
references
References 47 publications
0
32
0
Order By: Relevance
“…Special consideration should be taken to provide the highest-quality healthcare for older metastatic brain tumor patients and those from a non-home admission source. Evaluation of baseline health status and comorbid conditions should help guide surgical decision making and the consideration of possible non-operative management in frail older patients [ 47 , 48 ]. Our study also established surgery duration as an independent predictor for increased total hospital costs among metastatic brain tumor patients.…”
Section: Discussionmentioning
confidence: 99%
“…Special consideration should be taken to provide the highest-quality healthcare for older metastatic brain tumor patients and those from a non-home admission source. Evaluation of baseline health status and comorbid conditions should help guide surgical decision making and the consideration of possible non-operative management in frail older patients [ 47 , 48 ]. Our study also established surgery duration as an independent predictor for increased total hospital costs among metastatic brain tumor patients.…”
Section: Discussionmentioning
confidence: 99%
“…These findings have relevance to recently introduced initiatives by Medicare to provide less costly, better quality care using ‘bundles of care.’ The BPCI program recently introduced by Medicare in October 2015 is being evaluated by thousands of providers across the country in various conditions and in various episodes of care [ 10 ]. This care entails acute hospital care and the associated aftercare post-discharge (commonly 90 days after hospital discharge).…”
Section: Discussionmentioning
confidence: 99%
“…It was assumed that patients discharged home and not receiving additional care (e.g., SNF, rehabilitation, home care) in both LITT and craniotomy did not have complications, but this may not have been the case. However, a recent systematic review and meta-analysis comparing LITT to craniotomy in patients with high-grade tumors in or near areas of eloquence found that there were significantly lower complications and significantly more of the tumor ‘excised’ with LITT [ 10 ]. As noted here, these factors relate strongly to overall survival.…”
Section: Limitationsmentioning
confidence: 99%
See 1 more Smart Citation
“…58 Now that LITT has been developed, it is safer than resection in certain areas of the brain, with a 10% absolute risk reduction, as it is associated with less long-term neurologic morbidity and an increased rate of gross total resection compared to surgical resection. 79 …”
Section: Thermal Therapies In Brain Tumorsmentioning
confidence: 99%